Cardiac involvement in patients with rheumatic disorders: Data of the RHEU-M(A)R study. (1st December 2016) - Greulich, Simon; Kitterer, Daniel; Kurmann, Reto; Henes, Joerg; Latus, Joerg; Gloekler, Steffen; Wahl, Andreas; Buss, Sebastian J.; Katus, Hugo A.; Bobbo, Marco; Lombardi, Massimo; Backes, Maik; et al.
Abstract: Background: The diagnosis of cardiac involvement in rheumatic disorders is challenging due to its varying clinical presentation. Since clinical consequences range from immediate treatment changes to adverse long-term outcome, individual risk stratification is of great clinical interest. Primary aim was to evaluate the prevalence of cardiac involvement in patients with different rheumatic disorders using late gadolinium enhancement–cardiac magnetic resonance imaging (LGE-CMR). In addition, we sought to investigate if different rheumatic disorders would demonstrate different LGE patterns. Methods: Two-hundred-ninety-seven patients with rheumatic disorders were included and underwent LGE-CMR for work-up of cardiac involvement, which was defined by the presence of LGE in the myocardium. Patients were divided into five subgroups: 1) ANCA-associated vasculitis, 2) non-ANCA-associated vasculitis, 3) connective tissue disorders, 4) arthritis, and 5) sarcoidosis. Results: Mean ejection fraction in the overall population was 65%, with a mean age of 55 yrs. Prevalence of cardiac involvement in the five subgroups were as follows: 54% in the ANCA-associated vasculitis group, 22% in the non-ANCA-associated vasculitis group, 14% in the group with connective tissue disorders, 21% in the arthritis group, and 24% in sarcoid patients. Each of the five subgroups demonstrated a distinct pattern of LGE. Conclusion: There is a wide range in the prevalence of cardiac involvement in different rheumatic disorders (54%–14%). Different groups of rheumatic disorders demonstrate different patterns of LGE. Condensed abstract: Primary aim of the study was to evaluate the presence of cardiac involvement in patients with different rheumatic disorders using LGE-CMR. In addition, we sought to investigate if different rheumatic disorders would reveal different LGE patterns. In our 297 patients, the highest prevalence of cardiac involvement was found in patients with ANCA-associated vasculitis (54%), whereas the lowest prevalence was demonstrated in patients with connective tissue disorders (14%). Furthermore, different groups of rheumatic disorders demonstrate distinct patterns of LGE.